DAMPAK REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MATERI BANGUN DATAR KELAS V DI SDN LEBAKMUNCANG 1 - Lisna Susilawati; Rayi Siti Fitriani; Syarif Hendriana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the impact of implementing the Realistic Mathematics Education (RME) approach on elementary school fifth-grade students' mathematical problem-solving skills in geometry concepts. The research employed a quantitative quasi-experimental method with a Nonequivalent Control Group Design. The population comprised all fifth-grade students at SDN Lebakmuncang 1. Using a purposive sampling technique, the sample consisted of class V A (25 students) as the experimental group and class V B (25 students) as the control group. The experimental group received instruction using the RME model, whereas the control group was taught using the Contextual Teaching and Learning (CTL) model. Data were collected using a 20-item essay test measuring Polya's four problem-solving indicators, supplemented by observation and documentation. Instrument testing included validity, KR-20 reliability, difficulty level, and discrimination power analyses. Pretest and posttest data were analyzed descriptively and inferentially using prerequisite tests (Shapiro-Wilk normality and Levene's homogeneity) and hypothesis tests (Independent Samples t-Test or Mann-Whitney U-Test). Intervention effectiveness was calculated through N-Gain and Effect Size analyses using Cohen's d. The findings are expected to provide empirical evidence regarding the effectiveness of the RME approach in improving mathematical problem-solving ability in elementary geometry education.